Experiential Learning in TLE Cookery Towards Soft Skills Among Grade 10 Learners - Ramirez, Hazel D. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study investigates the relationship between experiential learning approaches in Technology and Livelihood Education (TLE) Cookery and the development of soft skills among Grade 10 students at Gaudencio B. Lontok Memorial Integrated School in Lipa City. Rooted in Kolb’s Experiential Learning Theory, the research explores how learning strategies—active experimentation, concrete experience, reflective observation, and abstract conceptualization—enhance students' work-related soft skills such as communication, numeracy, problem-solving, learning adaptability, and teamwork. Using a descriptive-correlational design and quantitative analysis, data were collected through surveys administered to 102 students. Findings revealed that experiential learning was positively perceived by students, particularly in fostering real- life engagement and reflective thinking. Among the four dimensions of experiential learning, concrete experience and reflective observation had the strongest associations with the development of soft skills. The study also found significant variations in perceptions and soft skill development when respondents were grouped by section, emphasizing the influence of instructional quality and classroom dynamics. The research underscores the value of integrating experiential strategies into the TLE curriculum to improve both hard and soft skill acquisition, thus preparing students for employment or entrepreneurial pursuits. Implications suggest that curriculum planners, teachers, and school administrators should prioritize hands-on learning approaches to enhance student competencies aligned with workforce demands.